The Effects of Enzyme Supplementation on Performance, Carcass Characteristics and Some Blood Parameters of Broilers Fed on Corn-Soybean Meal-Wheat Diets - Hajati, H.; Rezaei, M.; Sayyahzadeh, H. (International Journal of Poultry Science, 2009)
In a completely randomized design the effects of a multi-enzyme (Endo-feed-W) supplementation on performance, carcass characteristics and some blood parameters of Cobb 500 broilers fed on corn-soybean meal-wheat diets were studied. The enzyme levels added to the diets were 0.00% (control) and 500mg kg-1 DM. Enzyme supplementation significantly improved body weight gain, feed to gain ratio, relative growth, energy and protein efficiency from 11-28 d of age. Adding enzyme significantly increased body weight gain, decreased feed intake and improved feed to gain ratio, energy and protein efficiency from 29-44 d of age (p